2019
DOI: 10.1002/aenm.201803052
|View full text |Cite
|
Sign up to set email alerts
|

A Ternary Fe1−xS@Porous Carbon Nanowires/Reduced Graphene Oxide Hybrid Film Electrode with Superior Volumetric and Gravimetric Capacities for Flexible Sodium Ion Batteries

Abstract: Smart construction of ultraflexible electrodes with superior gravimetric and volumetric capacities is still challenging yet significant for sodium ion batteries (SIBs) toward wearable electronic devices. Herein, a hybrid film made of hierarchical Fe1−xS‐filled porous carbon nanowires/reduced graphene oxide (Fe1−xS@PCNWs/rGO) is synthesized through a facile assembly and sulfuration strategy. The resultant hybrid paper exhibits high flexibility and structural stability. The multidimensional paper architecture po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(131 citation statements)
references
References 54 publications
6
125
0
Order By: Relevance
“…TheS -H-Fe 2 O 3 /RGO delivered an excellent rate capability with highly reversible capacities of 1167, 1087, 1012, 936, and 701 mAh g À1 at 0.2, 0.5, 1, 2, and 5Ag À1 , respectively (Figure 5b S19) based on the following relationship: i p = av b ,w here i p and v are peak current and scan rate,r espectively,w hile aa nd b are variables,w ith the b-value determined from the slope of the plot of log i p versus log v. A b value of 0.5 indicates that the electrochemical process is diffusion-limited behavior, when b = 1.0, it indicates as urface-controlled capacitive process. [42][43][44][45][46][47] The b value of the S-H-Fe 2 O 3 /RGO was calculated to be 0.92 at scan rates from 0.1 to 2mVs À1 , which is higher than that of the L-H-Fe 2 O 3 /RGO (0.85) and the Fe 2 O 3 /RGO (0.71) (Figure 5c), demonstrating more dominant surface-controlled kinetics for the S-H-Fe 2 O 3 / RGO and in accordance with its remarkable rate performance.…”
Section: Resultsmentioning
confidence: 99%
“…TheS -H-Fe 2 O 3 /RGO delivered an excellent rate capability with highly reversible capacities of 1167, 1087, 1012, 936, and 701 mAh g À1 at 0.2, 0.5, 1, 2, and 5Ag À1 , respectively (Figure 5b S19) based on the following relationship: i p = av b ,w here i p and v are peak current and scan rate,r espectively,w hile aa nd b are variables,w ith the b-value determined from the slope of the plot of log i p versus log v. A b value of 0.5 indicates that the electrochemical process is diffusion-limited behavior, when b = 1.0, it indicates as urface-controlled capacitive process. [42][43][44][45][46][47] The b value of the S-H-Fe 2 O 3 /RGO was calculated to be 0.92 at scan rates from 0.1 to 2mVs À1 , which is higher than that of the L-H-Fe 2 O 3 /RGO (0.85) and the Fe 2 O 3 /RGO (0.71) (Figure 5c), demonstrating more dominant surface-controlled kinetics for the S-H-Fe 2 O 3 / RGO and in accordance with its remarkable rate performance.…”
Section: Resultsmentioning
confidence: 99%
“…In order to further increase the capacity, one effective strategy is to introduce other high‐capacity active materials into the graphene substrate. Lou's group fabricated a flexible and foldable Fe 1‐x S@PCNWs/rGO hybrid paper through a facile assembly and sulfuration strategy. As shown in Figure A, the hybrid paper could be randomly bent, rolled, twisted, and folded.…”
Section: Graphene‐based Electrodes For Flexible Metal‐ion Batteriesmentioning
confidence: 99%
“…A, Digital images for the appearance and flexibility (bending, rolling, twisting, and folding) of the Fe 1‐x S@PCNWs/rGO paper. B, Digital photos of the flexible SIB lightening a LED under various states . Copyright 2019, Wiley‐VCH.…”
Section: Graphene‐based Electrodes For Flexible Metal‐ion Batteriesmentioning
confidence: 99%
“…[26] Liu et al designed and fabricated at ernary FeS@porous carbon nanowires/reducedg raphene oxide (rGO) hybrid film anode throughs caleup assembly and sulfuration methodologies. [27] Li et al reported an efficient approach exploiting biomass as the precursorf or the preparation of 3D N/O-doped carbon frameworks with pyrolysis temperatures from 500 to 800 8Cb yu sing hydrothermala nd pyrolysis/activation methods. [28] Sun et al reported methods for porous carbon materials with Na nd S doping through the use of ionic liquidsf ollowed by pyrolization and activation at highert emperatures.…”
Section: Introductionmentioning
confidence: 99%